2021
DOI: 10.3390/ijerph18063121
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics and Interests of FeverApp Users

Abstract: The FeverApp Registry is a model registry focusing on pediatric fever using a mobile app to collect data and present recommendations. The recorded interactions can clarify the relationship between user documentation and user information. This initial evaluation regarding features of participants and usage intensity of educational video, information library, and documentation of fever events covers the runtime of FeverApp for the first 14 months. Of the 1592 users, the educational opening video was viewed by 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
4
0
4
Order By: Relevance
“…The video showed significant changes in some outcomes related to fever management in one study [ 31 ], so it may have already affected parental confidence and recommended management. On the other hand, Schwarz et al [ 33 ] examined the interactions of users of the FeverApp and showed that the main usage of the FeverApp is for documentation, not information.…”
Section: Discussionmentioning
confidence: 99%
“…The video showed significant changes in some outcomes related to fever management in one study [ 31 ], so it may have already affected parental confidence and recommended management. On the other hand, Schwarz et al [ 33 ] examined the interactions of users of the FeverApp and showed that the main usage of the FeverApp is for documentation, not information.…”
Section: Discussionmentioning
confidence: 99%
“…Feltárandók a betegségmérések során a gondozók állapotára vonatkozó adatok (kompetenciaérzés, magabiztosság) és ezek összefüggései a lázkezelés módjával. Rövid távú terveink között szerepel a LázBarát TM -hoz sok tekintetben hasonló, azonban a felhasználók rekrutálásában jelentősen eltérő németországi FeverApp-pal való összehasonlítás [26], míg hosszú távon applikációnk hatásvizsgálatát kettős vakvizsgálatként végeznénk. Az app állapotbesorolási algoritmusának specificitását és szenzitivitását a jövőben további szakértői Delfi-folyamat és gépi tanulás során adaptáljuk.…”
Section: Következtetésunclassified
“…Das Register-Protokoll [15] wurde veröffentlicht und beim Deutschen Register für Klinische Studien registriert (DRKS-ID: DRKS00016591). Weiterhin wurden erste App-basierte Nutzeranalysen veröffentlicht [16]. In diesen zeigt sich, dass die Dokumentation stärkere Anwendung findet als die Nutzung der Infothek oder des Lehrvideos zur Leitlinie der deutschen pädiatrischen Fachgesellschaften.…”
Section: S5unclassified
“…Neben systembedingten Informationen, wie z. B. Erfassungszeit oder Wechsel zwischen Ansichten in der App zur automatisierten Nutzeranalyse [16], werden basale Informationen zum Nutzer der App und zu den beobachtenden Kindern erfasst. Weiter existieren 14 Bereiche, die in einer Reihe oder freiwillig springend ausgefüllt werden können und einen Eintragszeitpunkt definieren.…”
Section: Datenelementeunclassified
See 1 more Smart Citation